2008
DOI: 10.1038/ng.165
|View full text |Cite
|
Sign up to set email alerts
|

Bmi1 is expressed in vivo in intestinal stem cells

Abstract: Bmi1 plays an essential part in the self-renewal of hematopoietic and neural stem cells. To investigate its role in other adult stem cell populations, we generated a mouse expressing a tamoxifen-inducible Cre from the Bmi1 locus. We found that Bmi1 is expressed in discrete cells located near the bottom of crypts in the small intestine, predominantly four cells above the base of the crypt (+4 position). Over time, these cells proliferate, expand, self-renew and give rise to all the differentiated cell lineages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
1,030
1
11

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,088 publications
(1,074 citation statements)
references
References 28 publications
32
1,030
1
11
Order By: Relevance
“…In this regard recent genetic lineage-tracing studies in the mouse have provided new evidence to support the existence of both rapid and slowly cycling intestinal stem cells. 1 Furthermore murine LRCs are most commonly found at position +4 crypts of the small intestine, 27 where the putative stem cell marker Bmi-1 is expressed 28,29 however Bmi-1 was not expressed in Barrett's glands from our patients (unpublished observations) and there are insufficient numbers of LRCs to precisely determine their cell position. It is possible that two stem cell populations co-exist in the gut in an overlapping way, one rapidly cycling and the other slowly cycling and that these may be interconvertable 29,30 .…”
Section: Discussionmentioning
confidence: 73%
“…In this regard recent genetic lineage-tracing studies in the mouse have provided new evidence to support the existence of both rapid and slowly cycling intestinal stem cells. 1 Furthermore murine LRCs are most commonly found at position +4 crypts of the small intestine, 27 where the putative stem cell marker Bmi-1 is expressed 28,29 however Bmi-1 was not expressed in Barrett's glands from our patients (unpublished observations) and there are insufficient numbers of LRCs to precisely determine their cell position. It is possible that two stem cell populations co-exist in the gut in an overlapping way, one rapidly cycling and the other slowly cycling and that these may be interconvertable 29,30 .…”
Section: Discussionmentioning
confidence: 73%
“…In the mouse small intestine, Bmi1-expressing cells can be localized by in situ hybridization as being located at cell position 4-5, counting from the bottom of the crypt, and lineage tracing from Bmi1-expressing cells suggests that these cells can also generate long-lived clones containing all the intestinal cell lineages [63].…”
Section: Markers Related To Stem Cell Functionmentioning
confidence: 99%
“…CBCs are actively cycling cells -nevertheless, they appear to function as stem cells; using a tamoxifen-activatable Cre recombinase knocked into the Lgr5 locus, it has been possible to find long-lived clones derived from Lgr5-positive cells that contained all small intestinal lineages, likewise in the large intestine [4]. A similar strategy based on Bmi1-positive cells, also generated multilineage clones, but the Bmi1-positive cells were located at cell position 4-5 [63]. Thus, in the mouse small intestine at least, we appear to have two distinct stem cell populations, rapidly cycling Lgr5 + CBC stem cells and a more slowly cycling Bmi1 + stem cell population at positions 4-5.…”
Section: Digestive Tractmentioning
confidence: 99%
“…Several cell markers with expression patterns that overlie this position have been described 12, 13, 14. Using a tamoxifen‐inducible Bmi1 Cre recombinase mouse, Sangiorgi et al demonstrated lineage tracing from cells at the +4 position 12.…”
Section: Stem Cell Identificationmentioning
confidence: 99%